Magnetic resonance cholangiopancreatography (MRCP) : biliary and pancreatic ducts - Manfredi, Riccardo (Springer Milan, 2013)
This book, based on the experience of a single large referral center, presents the characteristic findings obtained when using MR imaging and MR cholangiopancreatography (MRCP) to image the biliary tree and pancreatic ducts in a variety of disease settings. An introductory chapter is devoted to technical considerations, anatomy, and developmental anomalies. Subsequent chapters then present in detail the MR imaging and MRCP findings observed in choledocholithiasis, inflammatory and neoplastic disorders of the bile ducts, acute and chronic pancreatitis (according to etiology), and different pancreatic neoplasms. Dynamic MRCP with secretin stimulation is also illustrated, documenting both normal and abnormal responses of the pancreatic duct system to secretin. Readers will find this book to be an excellent aid to the interpretation of MR imaging and MRCP findings in patients with biliary and pancreatic disease.